Gestión Estratégica de las PYMES: Entre su Relevancia Socioeconómica y sus Debilidades Estructurales en México y Nuevo León. - Abreu, José Luis; Villarreal, Antonio Carlos Cantú; Rodríguez, Pablo Guerra (Revista Daena: International Journal of Good Conscience)
Small and medium-sized enterprises (SMEs) play a decisive role in the Mexican economy due to their broad presence within the business structure, their contribution to employment, and their impact on regional development. Yet this relevance coexists with structural weaknesses that limit their growth, sustainability, and competitiveness. This article aimed to analyze the socioeconomicrelevance of SMEs and the structural weaknesses that condition their performance in Mexico and, more specifically, in Nuevo León, from a strategic management perspective. The study was conducted under a qualitative approach, with a non-experimental design, descriptive and interpretive scope, and a documentary method based on the review and thematic analysis of academic and institutional sources. The findings show that SMEs are an essential component of the productive system and regional development; however, they continue to face persistent limitations related to access to financing, low formalization of strategic planning, technological gaps, centralized decisionmaking, and limited managerial capabilities. In the case of Nuevo León, although opportunities emerge from industrial dynamism and processes such as nearshoring, competitive and technological demands on these firms also become more intense. The article concludes that strengthening SMEs requires more contextualized strategic management models, as well as public policies and support mechanisms that foster their consolidation in increasingly complex economic environments.